Master of mimicry: Rare primary cutaneous anaplastic large cell lymphoma presenting as fungating parotid tumor–case report and review - Heng, Sophia Si Ling; Fatimah Mat Johar; Thevarasan Ganandran; Nurul Anis Mohd Fauzi; Faezahtul Arbaeyah Hussain; Wan Azman Wan Sulaimana (Elsevier Ltd, 2022)
Introduction Primary cutaneous anaplastic large cell lymphomas (PC-ALCL) are rare. They fall within non-Hodgkin's lymphomas spectrum. Commonly misdiagnosed, this malignancy involving the skin has favorable prognosis. To the best of our knowledge, this is the first reported case of PC-ALCL involving the parotid gland. This clinical presentation can mislead surgeons. We highlight this diagnostic conundrum. Case presentation A 73-year-old gentleman presented with two painless, ulcerating nodules over the right pre-auricular and angle of the mandible. Prior to that, he had right pre-auricular swelling that enlarged over a year. Skin nodules erupted few weeks before seeking treatment. Computed Tomography scan reported homogenously enhancing masses at posterior part of parotid gland's superficial lobe with diffuse lobe enlargement and no regional lymphadenopathy. A hypodense lesion at the liver indicated metastasis. Biopsy revealed PC-ALCL. He responded well to chemotherapy. Discussion PC-ALCL commonly presents as solitary nodules that can ulcerate over the head and neck region. Reports of PC-ALCL involving the eyelids, lips, and breast were found in our literature review. Multifocal lesions occur in 20% of cases. Malignant parotid tumors are aggressive and require parotidectomy which carry the risk of facial nerve injury. Treatment of PC-ALCL however, is local excision and radiotherapy for solitary lesions; and chemotherapy for those with extracutaneous spread. The 5-year survival rate is 90% in PC-ALCL. Conclusion PC-ALCL is a master of mimicry. To prevent serious morbidity, awareness regarding this entity as a differential diagnosis compared to the common malignant parotid tumors need to be raised.